The Geopolitical Context of Migrant Routes and Its Impact on Organised Crime in the Republic of North Macedonia - Mileski, Toni; Pacemska, Daniela (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
As a country with a specific geopolitical and geostrategic position, North Macedonia, positioned in the centre of the Balkan Peninsula, is subject to illegal migration and is located at the crossroads of migrant routes leading from Asia and Africa to Central and Western Europe. Therefore, the article makes an effort to answer two related questions. The first question refers to the geopolitical context of migrant routes and their impact on the increase in migrant smuggling, while the second one is the focus of migrant smuggling within organised crime groups. In terms of time, the research covers the period of the COVID-19 pandemic. The methodology of this paper is based on an analysis of policy documents from open sources. Also, the authors surveyed more than one hundred Macedonian police officers who work directly on the borders and engage in the suppression of smuggling migrants, and an in-depth interview with the head of the National Unit for Combating Migrant Smuggling and Trafficking in North Macedonia.